A multilayer polymer solid electrolyte membrane and its preparation method and application

By using a multi-layered polymer solid electrolyte separator in lithium batteries, using the combination of fiber crosslinking structure and metal-organic frame materials, the shortcomings of lithium batteries in high current charging and discharge and safety performance are solved, and high lithium ion is achieved Improved conductivity and mechanical properties reduce the risk of fire and explosion and simplify the process flow.

CN114824463BActive Publication Date: 2025-01-17FUJIAN NORMAL UNIV

Patent Information

Application Number
CN202210452083.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-27
Publication Date
2025-01-17
Estimated Expiration
2042-04-27

AI Technical Summary

Technical Problem

The heat generated by existing lithium batteries during charging and use causes unstable decomposition of the electrolyte, which increases the risk of swelling and fire explosion. The lithium ion transmission efficiency and mechanical properties of existing polymer solid electrolyte membranes are insufficient, making it difficult to meet the needs of the large amount of lithium ion transmission efficiency and mechanical properties. Current charge and discharge and safety performance requirements.

Method used

Using a multi-layered polymer solid electrolyte separator, fiber cross-linked structural material as a skeleton, metal-organic frame material is mixed with polymer to form a multi-layer structure of polymer-covered skeleton material, enhance mechanical properties and introduce a small amount Liquid electrolyte to increase lithium ion transfer rate.

Benefits of technology

It significantly improves lithium ion conductivity, lithium ion migration number, mechanical properties and flame retardant properties, extends the cycle life of lithium batteries and improves the theoretical specific capacity, and at the same time, the process is simple and suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824463B_ABST
    Figure CN114824463B_ABST
Patent Text Reader

Abstract

The present invention relates to a polymer solid electrolyte diaphragm with a multilayer structure and a preparation method and application thereof. The diaphragm structure is a multilayer structure of polymer layer / skeleton material layer / polymer layer, wherein the skeleton material layer is mainly a skeleton material and is also infiltrated by the polymer layer; the polymer layer is a polymer material with lithium ion conductivity. In the multilayer structure of the present invention, a small amount of liquid electrolyte remaining in the rich gaps of the metal-organic framework material tightly arranged in the skeleton material layer forms a liquid film, which can provide a liquid transmission channel when the solid electrolyte diaphragm transmits lithium ions, improve the lithium ion transmission rate and lithium ion migration number of the electrolyte diaphragm, and at the same time, the good mechanical strength and thermal stability of the fiber cross-linking structure can improve the mechanical properties and flame retardant properties of the polymer electrolyte diaphragm. The obtained lithium metal battery and lithium ion battery have a longer cycle life and a higher specific capacity. At the same time, the process of the present invention is simple and easy to operate, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of secondary lithium batteries, and in particular relates to a multi-layer structure polymer solid electrolyte diaphragm and a preparation method and application thereof. Background Art

[0002] With the rapid development of social economy, lithium batteries, including lithium-ion batteries and lithium metal batteries, have been rapidly developed and widely used, especially in electric vehicles, mobile phones and other electronic devices. In order to further meet the needs of social development, the capacity of batteries has been continuously improved, and the charging current has become larger and larger. These will cause the battery to generate a lot of heat during use and charging. This heat will make the battery electrolyte unstable and decompose, causing the battery to swell, and even there will be a risk of battery fire and explosion. The battery electrolyte and commercial polyethylene / polypropylene diaphragms are both flammable, so once a fire breaks out, it will spread rapidly and threaten the safety of the surrounding area. Now, the use of polymer solid electrolytes instead of liquid electrolytes can effectively deal with the above dangers. On the one hand, polymer solid electrolytes do not contain or only contain a small amount of liquid electrolytes, and have high electrochemical stability, which greatly reduces the risk of electrolyte decomposition. On the other hand, polymer materials do not have the flammability of liquid electrolytes, which can reduce the risk of battery fire and explosion. Therefore, polymer electrolyte membranes have been widely researched and developed in recent years. In order to match the current needs of energy storage devices, the following requirements are also put forward for polymer electrolytes: First, the polymer electrolyte needs to have high lithium ion conductivity and lithium ion migration number to ensure the performance of large current charging and discharging; second, the polymer electrolyte needs to have high thermal stability and flame retardant properties to improve the safety performance of the battery.

[0003] Most polymers with lithium ion conductivity have low lithium ion conductivity. The existing methods mainly improve the performance of polymer solid electrolyte membranes by adding nanomaterials to polymer matrices. Although the nanoparticles added by these methods can produce bonding interactions with the polymer matrix and improve the electrochemical properties and strength of the contact interface polymer to a certain extent, on the one hand, the amount of nanomaterials added is small, the main body of the polymer solid electrolyte membrane is still a polymer material, and the transmission of lithium ions still relies on the coupling-decoupling process with the polymer, without any essential improvement; on the other hand, the nanomaterials rely on hydrogen bonds between polymer molecules to enhance the mechanical properties of the polymer membrane to a limited extent; finally, the preparation process of most nanoparticles is complicated, which is difficult for industrial application and promotion. Compared with the polymer molecules using their interaction with lithium ions to conduct lithium ions, the transmission speed of lithium ions in liquid solvents has great advantages. If a similar lithium ion conduction method can be introduced into polymer solid electrolytes, it can provide a new way to improve the electrochemical performance of polymer electrolytes. At the same time, introducing skeleton materials to replace or bear external forces at the same time can directly share the forces acting on the polymer materials and enhance the mechanical stability of the diaphragm. These new methods are of great significance to the development of lithium batteries. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention proposes a multilayer polymer solid electrolyte membrane and its preparation method and application. The present invention selects a fiber cross-linked structure material as a skeleton, grows a metal-organic framework material in situ, and mixes it with a polymer to obtain a multilayer polymer membrane with a polymer-coated skeleton material. In the polymer solid electrolyte membrane, the internal fiber cross-linked structure skeleton can share the force of the membrane and enhance the mechanical properties of the membrane; and the abundant voids inside the in-situ grown metal-organic framework material can accommodate a small amount of electrolyte, and these small amounts of liquid electrolyte have a low risk of ignition, and due to the close contact between the metal-organic framework, a liquid channel can be formed to promote lithium ion transmission; at the same time, the physical stability of the skeleton material and the metal-organic framework material can improve the thermal stability and flame retardant properties of the polymer membrane. The obtained multilayer polymer solid electrolyte has high lithium ion conductivity and lithium ion migration number and excellent flame retardant properties, and the obtained lithium battery has a long cycle life and a high theoretical specific capacity; at the same time, the process has the advantages of simple process and easy operation, and is suitable for industrial promotion and application.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A multi-layered polymer solid electrolyte membrane comprises: a polymer matrix, a skeleton material and a lithium salt coated inside the polymer, forming a multi-layered structure of polymer layer / skeleton material layer / polymer layer; the skeleton material is obtained by in-situ growth of a metal-organic framework material on a fiber cross-linked structure material, wherein the metal-organic framework material is formed by a combination of a metal compound and an organic ligand. In the multi-layered polymer solid electrolyte membrane, the skeleton material and the polymer material are in full contact.

[0007] Furthermore, the thickness of the multi-layered polymer solid electrolyte membrane is 25-300 microns; the mass ratio of lithium salt to polymer matrix in the multi-layered polymer solid electrolyte membrane is 1:20-1:5.

[0008] The above-mentioned multilayer structure polymer solid electrolyte membrane is prepared by the following method:

[0009] (1) After the fiber cross-linked structure material is cleaned, it is placed in a mixed solution containing dissolved metal salts and organic ligands to allow the metal-organic framework material to grow in situ on its surface. The framework material is then taken out, cleaned and set aside.

[0010] (2) dissolving a polymer matrix and a lithium salt in a solvent to obtain a polymer solution, then soaking the obtained skeleton material in the polymer solution for a period of time and then taking it out, or pouring the polymer solution on the skeleton material, then drying the mixture of the polymer and the skeleton material to obtain a polymer-encapsulated skeleton material multilayer structure film of polymer / skeleton material / polymer;

[0011] (3) The multilayer structure film is immersed in a liquid electrolyte and then taken out and naturally dried for a period of time to obtain a multilayer structure polymer solid electrolyte membrane.

[0012] Furthermore, the fiber cross-linked structural material is a three-dimensional cross-linked integrated structure made of one or more fiber materials such as natural fiber (silk, wool, cotton, etc.), synthetic fiber (polyester fiber, polyacrylonitrile, etc.) and inorganic fiber (glass fiber, ceramic fiber, etc.) through weaving, knitting and spinning. The fiber materials in this structure are tightly entangled and have high mechanical strength.

[0013] Furthermore, the skeleton material is a fiber cross-linked structural material and a metal-organic framework material on its surface, wherein the metal-organic framework material is obtained by in-situ growth on the fiber surface and is tightly and continuously arranged on the fiber surface. The metal-organic framework material has abundant gaps that can retain a small amount of electrolyte. The tightly and continuously arranged metal-organic framework material allows a small amount of electrolyte to remain inside it to form a continuous liquid film, providing a liquid transmission channel for lithium ions, which can effectively improve the lithium ion conductivity and transmission number of the polymer electrolyte. At the same time, the fiber cross-linked structural material can improve the mechanical properties and flame retardant properties of the electrolyte diaphragm.

[0014] Furthermore, the in-situ grown metal-organic framework material is achieved by chemical reaction between metal compounds and organic ligands.

[0015] Furthermore, the polymer matrix is ​​selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polymethyl methacrylate, and polyethylene carbonate having the ability to conduct lithium ions.

[0016] Furthermore, the lithium salt is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium dioxalatoborate, and lithium oxalatodifluoroborate.

[0017] Furthermore, the metal salt is selected from one or more zinc salts, cobalt salts, magnesium salts or nickel salts soluble in water or organic solvents; the organic ligand is selected from one or more imidazole organic ligands and hydroxyterephthalic acid organic ligands.

[0018] Furthermore, by adjusting the metal salt, organic ligand, solvent selection and ratio, as well as the time and temperature of the fiber cross-linked structural material in the solution, the in-situ grown metal-organic framework material structure is made more uniform and arranged more closely, which is more conducive to the subsequent formation of the electrolyte membrane. After being soaked in the electrolyte, the polymer layer and the skeleton material layer will be filled with electrolyte, and after natural drying, the electrolyte in the polymer layer will completely evaporate, while a small amount of electrolyte will still remain in the rich pores of the metal-organic framework material in the skeleton material layer. These residual electrolytes can form a liquid membrane to provide a liquid channel for lithium ion transmission. The solid-state transmission rate in the polymer layer is significantly faster.

[0019] In order to obtain better results, the in-situ growth of the metal-organic framework material is carried out at a temperature between 10 and 40 degrees Celsius. The drying temperature of step (2) is 40 to 80 degrees Celsius, and the natural drying temperature of step (3) is 20 to 30 degrees Celsius. The polymer coating of the framework material means that the polymer uniformly wraps and infiltrates the framework material.

[0020] The present invention also provides application of the multilayer structure polymer solid electrolyte diaphragm in a secondary lithium battery.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention utilizes the abundant voids in the metal-organic framework material to retain a small amount of liquid electrolyte, and when the framework materials are arranged in close contact with each other, the remaining electrolyte can form a liquid film for lithium ion transmission. This transmission method significantly increases the rate of lithium ion transmission compared to utilizing the interaction between polymers and lithium ions.

[0023] (2) The present invention utilizes fiber cross-linked structural materials as carriers to in-situ grow metal-organic framework materials, thereby ensuring close contact between the framework materials and providing good mechanical strength.

[0024] (3) The multilayer structure proposed in the present invention can not only utilize the good contact between the polymer material and the electrode, but also optimize the electrochemical performance of the solid electrolyte membrane by controlling the thickness of the skeleton material layer and the polymer layer.

[0025] (4) The metal-organic framework material with large specific surface area and rich functional groups prepared by the present invention can form a strong physical and chemical reaction with the polymer to reduce the lithium ion transmission resistance between the polymer layer and the skeleton layer.

[0026] (5) The multilayer polymer solid electrolyte membrane described in the present invention can effectively improve the lithium ion conductivity, lithium ion transference number, mechanical properties, thermal stability and flame retardancy of the electrolyte membrane.

[0027] (6) The multilayer polymer solid electrolyte separator described in the present invention can improve the specific capacity and capacity retention rate of lithium-ion batteries.

[0028] (7) The polymer electrolyte membrane of the present invention can improve the cycle life of lithium metal batteries.

[0029] (8) The preparation method of the present invention can be operated using conventional heating and stirring equipment, and the process is easy to operate and simple in process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a SEM image of the skeleton material loaded with the metal-organic framework material in Example 1;

[0031] Figure 2 is a cross-sectional SEM image of the multilayer structure polymer solid electrolyte membrane in Example 1;

[0032] Figure 3 1 is a voltage-time curve diagram of a lithium metal symmetric battery with a pure polymer solid electrolyte membrane and a multilayer polymer solid electrolyte membrane in Example 1;

[0033] Figure 4 1 is a cycle stability diagram of lithium ion batteries with pure polymer solid electrolyte membrane and multilayer polymer solid electrolyte membrane in Example 1;

[0034] Figure 5 is a flame retardant performance diagram of the multilayer structure polymer solid electrolyte membrane in Example 1;

[0035] Figure 6 This is an optical photograph of the skeleton material after the in-situ growth of the metal-organic framework material in Example 2. DETAILED DESCRIPTION

[0036] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. In the examples, unless otherwise specified, the technical means used are conventional technical means in the art.

[0037] Example 1

[0038] Preparation of a multilayer polymer electrolyte membrane:

[0039] (1) 0.824 g of zinc nitrate hexahydrate and 1.825 g of 2-methylimidazole were dissolved in 45 ml of methanol respectively and then mixed. Then, a cleaned glass fiber cloth was quickly immersed in the solution. The solution was stirred at 30 degrees Celsius for 24 hours, and then the glass fiber cloth was taken out, cleaned and dried at 60 degrees Celsius to obtain a skeleton material.

[0040] (2) 1 g of polyvinylidene fluoride-hexafluoropropylene, 0.1 g of polyethylene oxide and 0.5 g of lithium bis(trifluoromethanesulfonyl)imide were dissolved in 20 ml of acetone to obtain a polymer solution. The skeleton material prepared above was cut into discs and immersed in the polymer solution. After it was completely soaked, it was taken out and dried to obtain a multilayer structure polymer membrane. The pure polymer control sample was obtained by scraping the polymer solution and then drying it.

[0041] (3) The multilayer structure polymer membrane and the pure polymer membrane were then immersed in a lithium-sulfur battery electrolyte for 12 hours and then taken out of the glove box and allowed to stand for 6 hours to obtain a multilayer structure polymer solid electrolyte and a pure polymer solid electrolyte.

[0042] Effect verification

[0043] The prepared skeleton materials and multilayer polymer solid electrolytes were characterized. Figure 1 From the SEM photos, we can see that the fiber surface of the skeleton material is covered with granular metal-organic framework materials, and these particles are in close contact. Figure 2 It can be seen that the above multi-layer structure polymer solid electrolyte is divided into three layers, namely polymer layer / skeleton material layer / polymer layer, wherein the polymer layer and the skeleton material layer are in close contact, and the polymer layer is relatively thin.

[0044] The prepared multilayer polymer solid electrolyte and the comparison sample pure polymer solid electrolyte were assembled into symmetrical batteries. Figure 3 From the voltage-time curve, it can be seen that the multilayer polymer solid electrolyte shows a smaller overpotential and a longer cycle life of more than 2000 hours, which is mainly attributed to the new lithium ion transmission form introduced by the liquid film formed by the skeleton material layer in its multilayer structure. At the same time, the glass fiber cloth improves the mechanical properties of the polymer electrolyte and can also form a certain inhibitory effect on lithium dendrites. Further, the lithium-ion battery was assembled with NCM811 positive electrode material to test the battery cycle stability. Figure 4 The long cycle performance of the battery in the experiment shows that the battery assembled with multilayer polymer solid electrolyte has significantly improved in initial capacity and cycle stability. Figure 5 It can be seen that the multilayer polymer solid electrolyte has good flame retardant properties, and there is no ignition or obvious ablation after combustion. This is provided by the good thermal stability of the main skeleton material layer in the multilayer polymer membrane.

[0045] Example 2

[0046] Preparation of a multilayer polymer electrolyte membrane:

[0047] (1) 0.807 g of cobalt nitrate hexahydrate and 1.825 g of 2-methylimidazole were dissolved in 45 ml of methanol respectively and then mixed. Then, a cleaned glass fiber cloth was quickly immersed in the solution. After the solution was stirred for 24 hours, the glass fiber cloth was taken out, cleaned and dried to obtain a skeleton material.

[0048] Preparation of polymer electrolyte membrane: Same as Example 1

[0049] Depend on Figure 6 It can be seen that after the cobalt-based metal-organic framework is in situ grown on the glass fiber cloth, the fiber cross-linking structure on the skeleton material is not as clear as before, indicating that the metal-organic framework material has grown on the fiber. At the same time, there is no obvious difference in the skeleton material, indicating that the cobalt-based metal-organic framework material completely and evenly covers the glass fiber cloth.

[0050] Example 3

[0051] Preparation of a multilayer polymer electrolyte membrane:

[0052] (1) 0.807 g of cobalt nitrate hexahydrate and 1.825 g of 2-methylimidazole were dissolved in 45 ml of methanol respectively and then mixed. Then, the cleaned polyacrylonitrile felt was quickly immersed in the solution. After the solution was stirred for 24 hours, the felt was taken out, cleaned and dried to obtain a skeleton material.

[0053] (2) 1 g of polyethylene oxide is dissolved in 20 ml of acetone to obtain a polymer solution. The skeleton material prepared above is cut into discs and immersed in the polymer solution. After the discs are completely soaked, they are taken out and dried to obtain a multilayer structure polymer membrane.

[0054] (3) The multilayer polymer separator was then immersed in a lithium-ion battery electrolyte for 12 hours and then taken out of the glove box and allowed to stand for 6 hours to obtain a multilayer polymer solid electrolyte.

[0055] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A multilayer polymer solid electrolyte membrane, characterized in that: It includes a polymer matrix, and a skeleton material and a lithium salt coated inside the polymer matrix; The preparation method of the skeleton material is: in-situ growing a metal-organic framework material on a fiber cross-linked structural material to obtain the skeleton material, wherein the metal-organic framework material is formed by combining a metal compound and an organic ligand; The method for preparing the multilayer polymer solid electrolyte membrane comprises the following steps: (1) After cleaning the fiber cross-linked structure material, the fiber cross-linked structure material is placed in a mixed solution containing a dissolved metal salt and an organic ligand and allowed to stand to in situ grow a metal-organic framework material on its surface to obtain a skeleton material; (2) dissolving a polymer having lithium ion conductivity and a lithium salt in a solvent, then impregnating the skeleton material obtained in step (1) therein, and then drying the mixture of the polymer and the skeleton material to obtain a multilayer structure film of the polymer-coated skeleton material; (3) The multilayer structure film obtained in step (2) is immersed in a liquid electrolyte, and then taken out and naturally dried to obtain a multilayer structure polymer solid electrolyte membrane.

2. The multilayer polymer solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of lithium salt to polymer matrix is ​​between 1:20 and 1:

5.

3. The multilayer polymer solid electrolyte membrane according to claim 1, characterized in that: The fiber cross-linked structural material is made of one or more of natural fibers, synthetic fibers and inorganic fibers through a method selected from the group consisting of weaving, knitting and spinning; the metal compound is one or more of zinc nitrate, zinc acetate, zinc sulfate, zinc chloride, cobalt nitrate, cobalt acetate, cobalt chloride and cobalt sulfate; and the organic ligand is one or more of imidazole organic ligands.

4. The multilayer polymer solid electrolyte membrane according to claim 1, characterized in that: The polymer matrix is ​​one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polymethyl methacrylate, and polyethylene carbonate with lithium ion conductivity; the lithium salt is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium dioxalatoborate, and lithium oxalatodifluoroborate.

5. The multilayer polymer solid electrolyte membrane according to claim 1, characterized in that: The solvent in step (2) is one or more of water, alcohols, N,N-dimethylformamide and acetone.

6. The multilayer polymer solid electrolyte membrane according to claim 1, characterized in that: The liquid electrolyte in step (3) is a lithium-sulfur battery electrolyte or a lithium-ion battery electrolyte.

7. Use of the multilayer polymer solid electrolyte membrane as claimed in any one of claims 1 to 6 in a lithium battery.

Citation Information

Patent Citations

  • Lithium-sulfur battery all-solid-state electrolyte and preparation method thereof

    CN105826602A

  • Solid electrolyte and preparation method and application thereof

    CN112397772A

Cited By

  • Preparation method and application of electrospinning hybrid nanofiber diaphragm

    CN116544608A

  • Preparation method and application of electrospun hybrid nanofiber separator

    CN116544608B